1992
DOI: 10.1136/vr.131.22.501
|View full text |Cite
|
Sign up to set email alerts
|

Causes of trauma in broilers arriving dead at poultry processing plants

Abstract: A post mortem examination was made on 1324 broiler carcases which arrived dead after being transported to six processing plants. The carcases were dissected and evaluated for trauma and obvious cause of death. Of the birds sent to the plants on the day of collection 0.19 per cent arrived dead and 35 per cent of these were thought to have died as a result of trauma. Haemorrhage associated with dislocation of the femur at the hip was the most common cause of trauma. Ruptured livers and crushed heads were other i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…The mean DOA percentage of hens and roosters found in our study was 0.925%. This figure is higher than values reported by Gregory and Austin (1992), Nijdam et al (2004) and Vecerek et al (2006a) for broilers, Voslarova et al (2006) for turkeys and Vecerek et al (2006b) for pigs. The DOA of hens and roosters is an important value that demonstrates deficiencies in hen and rooster welfare during their transport to poultry processing plants.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The mean DOA percentage of hens and roosters found in our study was 0.925%. This figure is higher than values reported by Gregory and Austin (1992), Nijdam et al (2004) and Vecerek et al (2006a) for broilers, Voslarova et al (2006) for turkeys and Vecerek et al (2006b) for pigs. The DOA of hens and roosters is an important value that demonstrates deficiencies in hen and rooster welfare during their transport to poultry processing plants.…”
Section: Discussioncontrasting
confidence: 55%
“…They reported the mean percentage of birds dead on arrival (DOA) to processing plants at 0.46. Causes of trauma in broilers arriving dead at poultry processing plants were also investigated by Gregory and Austin (1992). They found 0.19% of birds dead on arrival to processing plants.…”
mentioning
confidence: 99%
“…Traumas resulting from improper handling were described by Weeks and Nicol (2000) who reported up to 23% of laying hens with broken limbs after they were unloaded from the transport crate. Gregory and Austin (1992) found that trauma was the cause of death of 35% of broilers dead on arrival to the six processing facilities they were monitoring. Monitoring broilers during live haul, observed that injuries inflicted to the birds during loading and handling were the primary cause of their death on arrival at the slaughterhouse.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the application of 120 mA electrical current, which can cause the rupture of intramuscular blood vessels and blood retention in muscle tissue (Gregory & Austin, 1992;Lambooij et. al., 1999).…”
Section: Exposure To Carbonic Gas Enriched Atmosphere or Electrical Wmentioning
confidence: 99%